Sonographic Measurement of Fetal Pinna Length in Normal Pregnancies - Joshi, K S; Chawla, C D; Karki, S; Shrestha, N C (Kathmandu University Medical Journal, 2012)
Background Many studies have emphasized on fetal pinna measurements and morphologic features to use this structure as an additional marker for fetal chromosomal anomaly. Objectives To assess relationship between fetal pinna length and gestation age and develop a nomogram. To assess relationship between fetal pinna length and head circumference and biparietal diameter. Methods Fetal pinna measurements from the tip of helix to the end of lobe were obtained prospectively in 850 singleton pregnant women between 15 and 40 weeks’ gestation Normal case was defined as normal sonographic findings during examination and normal infant examination at birth or both. Final study population was 787. The relationship between gestational age in weeks to pinna length in millimeters was analyzed by simple linear regression. Correlation of fetal ear length measurements with gestational age, biparietal diameter and head circumference were also obtained. Results Linear relationships were found between fetal pinna length and gestational age [Pinna Length (mm)=1.044xGestational age (weeks) -3.857]. A nomogram of normal pinna length was obtained. High correlation was found between pinna length and gestational age (r=0.942; p< 0.001), pinna length and head circumference (r=0.931; p< 0.001). Significant correlation was found between pinna length and biparietal diameter (r=0.934; p=0.004) Conclusions The results of this study provide a nomogram for fetal pinna. The study also provides relationship and good correlation between pinna length and other biometric measurements. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6288 Kathmandu Univ Med J 2011;9(2):49-53